Salesperson Behavior and Customers Satisfaction in the Hospitality Industry: An Exposition of Selected Restaurants in Enugu Metropolis - Okolo, Victor; Mmamel, Zita (Journal of Marketing Studies, 2022)
Purpose: This paper studied the effect of salesperson behaviuor on customer satisfaction in the services industry. The specific objectives were firstly to determine the relationship between salesperson ethical selling behaviuor in delivering services and customer satisfaction in the services industry. Secondly, to ascertain the relationship between salesperson smart selling behaviour in delivering services and customer satisfaction in the services industry. Methodology: The study comprises customers of elected restaurant in Enugu metropolis whose population is unknown. Cochran's sample size determination formula was used to determine the sample size of 384. Survey method was used to distribute structured questionnaires to the 384 respondents who eventually retuned 300 well filled questionnaires. For the reliability of the study, Cronbach's alpha was used and the value of 0.784 was determined. Analysis of data was done using Pearson Product Moment correlation statistical tool. Results: Findings revealed that there is a significant positive relationship between salesperson ethical selling behaviour in delivering services and customer satisfaction. Similarly, it was revealed that there is a significant positive relationship between salesperson smart selling behaviour in delivering services and customer satisfaction. The implication of this finding is that if salespersons continue with these pleasant approaches, satisfied customers will make repeat purchase and transform into loyal customers. Unique Contribution to Theory, Practice and Policy: Therefore, restaurant management should lay more emphasis on improving salesperson behaviour to satisfy customers and improve organizational performance. Also, salespersons should be taught to be innovative in the manner they deliver restaurant services to enhance customer value.